Representing Violence in Lionel Asbo by Martin Amis: ‘Extremely Lout and Incredibly Gross’ - Anne-Laure Fortin-Tournès (Sillages Critiques)
The purpose of this paper is to probe into the representation of violence in Martin Amis’s novel, so as to uncover the mechanisms whereby Amis’s excessive, oralised and transgressive language conveys the violent experience in its forceful impact, which is brought to the reader through symbolic means. Amis’s idiosyncratic anti-hero, Lionel Asbo, plays the role of a catalyst of violence in a novel where incest, teenage pregnancy and dodgy dealings have become the rule in a ghettoized London. But beyond the representation of ubiquitous forms of social violence, however, it is Amis’s own idiosyncratic style that introduces transgressive violence into the novel, as it allows for an imagined London underworld to surface in the text. This presentation will analyse the textual devices responsible for the effects of violence in the novel, their connection to the representation of the failure of social and symbolic links, and the rhetoric of excess which muscles them up. The question of the reception of textual violence will underscore our analyses, which will focus on the way the text holds the reader a hostage to its fictional apparatus.